Elementary Science Teachers’ Perceptions of Educational Reform in Relation to Science Teaching in Jordan - Qablan, Ahmad; Jaradat, Suhair; Al-Momani, Ibrahim (Jordan Journal of Educational Sciences, 2010)
This study aims at evaluating elementary science teachers’ perceptions of the educational reform movement in Jordan with regard to their teaching practices. Data were collected from 87 elementary science teachers by means of an open-ended questionnaire and later interviews with 4 teachers. Analysis of the responses indicated that teachers see reform as a necessity, but they lack a common understanding of the purpose of the reform in relation to their science teaching practices.